Power up your creativity ignite your creative spark, develop a productive practice, set goals and achieve your dreams - Taylor, Rachael (Quarry Books, 2023)
Written by designer and creative educator Rachael Taylor, Power Up Your Creativity is a guide to cultivating a positive and productive creative path, from how to develop creativity, to building a productive practice, to achieving success (and defining on your own terms what that means/looks like).
Includes bibliographical references and index. - Description based on print version record
Keywords: Design -- Vocational guidance; Creative ability in business; Design; Orientation professionnelle; Créativité dans les affaires; Design; Vocational guidance